2018
DOI: 10.2215/cjn.11871017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Progression of Chronic Kidney Disease in Black and White Individuals with Type 2 Diabetes

Abstract: Black participants enrolled in a randomized controlled trial had lower rates of incident CKD compared with white participants. Rates of eGFR decline, microalbuminuria, macroalbuminuria, and kidney failure did not vary by race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
(49 reference statements)
1
17
0
2
Order By: Relevance
“…It has been reported that racial inequity, seen especially in North Americans with diabetic nephropathy, has disappeared when Afro-Americans were subjected to the same glucose control as Caucasians. 30 The male sex is usually associated with worse renal outcomes but this was not found in this cohort, possibly due to the small number of men included. 29,31…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that racial inequity, seen especially in North Americans with diabetic nephropathy, has disappeared when Afro-Americans were subjected to the same glucose control as Caucasians. 30 The male sex is usually associated with worse renal outcomes but this was not found in this cohort, possibly due to the small number of men included. 29,31…”
Section: Discussionmentioning
confidence: 70%
“…Whatever the reasons for this disparity, standardized interventions and improved healthcare delivery in these high‐risk individuals is required to reduce the variations in renal outcomes in these populations. In a recent post hoc analysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial looking at the longitudinal change in eGFR, time to development of microalbuminuria, macroalbuminuria, incident CKD, and kidney failure or serum creatinine >3.3 mg/dL, it was noted that even though the mean values of systolic blood pressure, glycated haemoglobin (HbA1c) microalbuminura, macroalbuminira and serum creatinine levels were higher in black participants at baseline, black and white participants achieved similar rapid improvement of both clinical variables, which were maintained during study follow‐up. This suggests that optimization of the delivery of diabetes care prior to the development of CKD may lead to similar short‐term kidney outcomes, irrespective of race.…”
Section: Discussionmentioning
confidence: 99%
“…Blacks were adequately represented, making up 19% of participants in the ACCORD trial. They had higher-risk clinical features at baseline, including higher levels of systolic BP and hemoglobin A1c as well as more frequent macro-and microalbuminuria (5). Contrary to the original study hypothesis, the rate of eGFR decline was not greater in blacks than whites starting from a normal eGFR.…”
mentioning
confidence: 58%
“…Blacks constitute 7% of overall clinical trial participants, although they make up 13% of the United States population (4). In this issue of the Clinical Journal of the American Society of Nephrology, Gerber et al (5) report a post hoc analysis of CKD risks in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) clinical trial by black versus white race (6). The ACCORD trial participants' diabetes care was standardized by the clinical trial format so that, as much as possible, they received comparable treatment consistent with clinical practice guidelines at the time, irrespective of self-identified race (6).…”
mentioning
confidence: 99%